Analysis of Average Flow Velocity and the Transformation of Flow Symmetry of Selected Fluid Samples in a Cylindrical Bifurcated Channel - Egbo A. Chijioke; Abbey M. Tamunoimi; Opuene D. Ogisobo; Wosu E. Nwonodi; Ashaka O. Godspower; Cookey S. Praise (PT FORMOSA CENDEKIA GLOBAL, 2022)
Research interest in the field of bifurcation and its role in flow distribution and recovery has grown greatly in the past two decades. In this study, data obtained from an experimental investigate of the flow of water, diesel oil, crude oil and peanut oil representing the following categories of fluid samples, polar solvent, as they are allowed to flow through a geometrical glass cylindrical tube with the following angles 10o, 20o, 30o, 40o, 50o, and 30o. and the designated volumes of 100ml, 200ml, 300ml, 400ml and 500ml of the fluid samples were recovered, results obtained how water representing polar solvent as a consequences of its properties can easily attain maximum average velocity, results also show how we can predict the average velocity of a fluid sample with known Specific Gravity (S.G), finally our result further shows how the flow symmetry in the branched channels changed from the conventional flow symmetry in a straight pipe.